A novel risk calculator to predict outcome after surgery for symptomatic spinal metastases; use of a large prospective patient database to personalise surgical management. (January 2019) - Choi, David; Pavlou, Menelaos; Omar, Rumana; Arts, Mark; Balabaud, Laurent; Buchowski, Jacob Maciej; Bunger, Cody; Chung, Chun Kee; Coppes, Maarten Hubert; Depreitere, Bart; Fehlings, Michael George; Kawahara, Norio; et al.
Abstract: Aim: Surgery for spinal metastases can improve symptoms, but sometimes complications can negate the benefits. Operations may have different indications, complexities and risks, and the choice for an individual is a tailor-made personalised decision. Previous prognostic scoring systems are becoming out of date and inaccurate. We designed a risk calculator to estimate survival after surgery, to inform clinicians and patients when making management decisions. Methods: A prospective cohort study was performed, including 1430 patients with spinal metastases who underwent surgery. Of them, 1264 patients from 20 centres were used for model development using a Cox frailty model. Calibration slope, D-statistic and C-index were used for model validation based on 166 patients. Follow-up was to death or minimum of 2 years after surgery. Pre-operative indices (examination findings, pain, Karnofsky physical functioning score, and radiology) were assessed. Results: An algorithm to predict survival was constructed including the tumour type, ambulatory status, analgesic use, American Society of Anesthesiologists score, number of spinal metastases, previous radiotherapy or chemotherapy, presence of visceral metastases, cervical or thoracic spine involvement, as predictors. An Internet-based risk calculator was developed based on this algorithm, with similar or improved accuracy compared to other validated prognostic scoring systems (C-index, 0.68; 95% confidence interval, 0.63––0.73, and calibration slope, 1.00; 95% confidence interval, 0.68––1.32). Conclusion: A large, prospective, surgical series of patients with symptomatic spinal metastases was used to create a validated risk calculator that can help clinicians to inform patients about the most appropriate treatment plan. The calculator is available atwww.spinemet.com . Highlights: Surgery for symptomatic spinal metastases takes many forms. Choice of operation depends on indications balanced by the patient's prognosis. Previous systems for estimating prognosis are now outdated. Risk calculators allow a contemporary estimation of survival. We developed an Internet-based risk calculator for survival after spine surgery.